Implementation of the Problem-Based Learning Model and Its Effect on Accounting Learning Outcomes During the COVID-19 Pandemic - Imran, Ahmad Fadhil; Ngampo, M. Yusuf A.; Ardiansyah, Ardiansyah (FKIP - Universitas Riau, 2022)
The transition from face-to-face learning to distance learning has decreased student learning outcomes. Departing from this phenomenon, this research is presented as an effort to overcome various obstacles experienced by teachers and students during the COVID-19 pandemic. The researcher offers a model that can be used in virtual learning activities. Beginning with finding out the extent of the influence of the problem-based learning (PBL) model on accounting learning outcomes in class X Accounting 1 students at SMK YPKK Limbung. Research data obtained from the results of the test, observation, and documentation. Then analyzed using t-test which consists of simple linear regression analysis and product moment correlation. The findings in this experimental study resulted in a simple linear regression equation model with a value of Y=33,012+4.283X and a correlation coefficient value of 0.580. After students received learning using the PBL model through distance learning and were given a post-test, their learning outcomes also increased. In other words, the implementation of the PBL model has a significant and positive effect on accounting learning outcomes during the COVID-19 pandemic.